Clinical applicability of Nursing Outcomes related to breastfeeding establishment in the Neonatal Intensive Care Unit - Suellen Cristina Dias Emidio; Henrique Ceretta Oliveira; Sue Moorhead; Ana Railka de Souza Oliveira-Kumakura; Elenice Valentim Carmona (Rev Rene)
Objective: to analyze clinical changes in the breastfeeding process in the Neonatal Intensive Unit Care using the Nursing Outcomes Classification. Methods: this longitudinal and prospective study was conducted in a public hospital at Neonatal Intensive Unit Care in Brazil. The sample consisted of 61 mother-infant dyads evaluated three times during breastfeeding by trained nurses who applied the Nursing Outcomes Classification scales. Statistical analysis was performed using Generalized Estimating Equation Models. Results: most indicators of the two Nursing Outcomes studied presented a similar frequency of scores of 4 and 5. It was observed that in most indicators, there were clinical changes throughout the evaluations over time; however, the indicators related to the mother presented a higher risk of scoring 4 and 5 on the Likert scale. Conclusion: the Nursing Outcomes Classification outcomes and indicators included successfully evaluated the clinical evolution of mother-infant dyads and proved to be applicable for use in Neonatal Intensive Unit Care. Contributions to practice: nurses can use the indicators to assess the quality of the proposed interventions.